Between self-determination and social technology: Medicine, biopolitics and the new techniques of procedural management - Braun, Kathrin (ed.) (New Burnswick, 2011)
The book critically examines how concepts such as self-determination, participation, ethics, or dialogue, developed not least by the feminist movement and directed against repression, heteronomy and professional paternalism, have been integrated into new contexts and transformed into new social technologies. Crossing a variety of fields from birthing, genetic counselling, living wills, hospital ethics, to population policies and politics of biomedicine, it shows that medicine and medicine-related policies and practices form crucial arenas of these transformations. What we see emerging is procedural management as a new set of social techniques. With a preface by William Ray Arney.
Keywords: Social engineering